JENIS DAN SIGNIFIKANSI PERTANYAAN GURU DI DALAM INTERAKSI KELAS BAHASA INGGRIS - Siti Aisah Ginting (BAHAS, 2018)
This article is about the kinds of questions and their role & function. The research design of this research is descriptive qualitative. The data are teachers’ questions which were occurred in the process of teaching and learning. The data was analyzed based on Kenchak & Eggen’s theory. Based on the analysis, it was found that display questions dominated the teachers’ questions and it was followed by referential and yes/no questions. Then, the role & function of teachers’ questions was dominated by diagnostic and it was followed by instructional and motivator questions. It was defined that teachers’ questions were still in the low level, that is the teacher wanted to know whether the students were able to answer the questions or not.